Survey of springtime Arctic bird migration in Vyborg in 1988–2008 and in Kurortny District in 1992–2001 - Kontiokorpi, Jari; Rusanen, Pekka (Finnish Environment Institute, 2015)
Finnish South Karelian birdwatchers observed the migration of arctic waterfowl and shorebirds in Vyborg every spring for 21 years, and in Kurortny District for eight years. The monitoring data of these expeditions covers nearly 3,000 observation hours during May and June in years 1988–2008. It was found out, that a large proportion of arctic waterfowl populations migrate through Vyborg and Kurortny areas, and that a part of these also stage in the areas. Concerning several species, the variation in annual sums of migrators reflected population developments in the arctic breeding areas, and also supported the estimations of wintering populations of the Baltic Sea. Expeditions collected a lot of monitoring data about the migration; daily rhythm, directions and routes, as well as intensity and timing of the migration. Clear differences between both species and observation areas were noticed in the dynamics, routes and intensity of the migration.